1577. Evaluation of a Routine Screening Program with Tuberculin Skin Testing on Rates of Detection of Latent Tuberculosis Infection and Prevention of Active Tuberculosis in Patients with Multiple Myeloma at a Canadian Cancer Center. (26th November 2018) - Gitman, Melissa; Vu, James; Nguyen, Tram; Rotstein, Coleman; Chen, Christine
Abstract: Background: Due to chemotherapy induced T-cell dysfunction, patients being treated for multiple myeloma (MM) are at high risk for reactivation of LTBI; however, the optimal screening strategy in this patient population has not been well described. The objective of this study was to assess the number of patients treated for LTBI both before and after the introduction of a consistent tuberculosis skin test (TST) screening program for patients with MM at our cancer center. Methods: We carried out a retrospective observational study of adult patients treated at our cancer hospital for MM with autologous hematopoietic stem cell transplantation and who also had a TST results available from January 1, 2013–December 31, 2014. Baseline demographic characteristics, results of TST and LTBI therapy were collected. This cohort was compared with a pre-intervention cohort of sporadically tested patients from January 1, 2008–December 31, 2009. Results: During the post-intervention period, 170 patients with MM had a TST. At the time of TST, 113 (66.4%) patients had a lymphocyte count ≥1.0 × 10 9 /L. Fourteen patients (8.2%) had positive Results. There were also 16 patients with radiographic evidence of prior granulomatous disease on either CXR or chest CT In these 16 patients, 12 (75%) with positive radiographic findings had negative TST Results. Notably, 7//12 (58.3%) had a lymphocyte count ≤1.0 × 10 9 /L at the time of testing. Eleven patients with positive TST results and two with positive radiographic results alone were treated for LTBI. There was one case of active TB diagnosed in a patient with a negative TST. There were no TSTs performed in the pre-intervention cohort and no cases of active TB were documented. Conclusion: A significant portion of our MM patients may benefit from LTBI therapy. A targeted program combining evaluation of host risk factors, imaging findings and screening tests would optimize LTBI diagnosis and management and may be effective in preventing the development of active TB. Disclosures: All authors: No reported disclosures.